Estratigrafía del Grupo Baqueró, Patagonia (provincia de Santa Cruz, Argentina) (Ameghiniana, 2014)
The stratigraphy of early Cretaceous strata in the central area of Santa Cruz Province has been a matter of study since the time when E.W. Berry published his first paleobotanical descriptions in 1924. Detailed sedimentological a nd petrographica 1investiga tions performed d uring recent years in the area of Meseta Baqueró, Bajo Tigre and Anfiteatro de Ticó localities have been added to the available paleontological information. It is now possible to present a new strabgraphic interpretabon of the sequence that has been previously referred to the Baqueró Forrnation. This unit is now considered at a higher rank, Baqueró Croup, that includes, from bottom to top the fol1owing forrnations: Anfiteatro de Ticó, Bajo Tigre and Punta del Barco. The stratotypes for each unit are located and the main lithofacies are described and interpreted. Fossil plant assemblages are placed in this new stratigraphic context and related to paleoenvironments that were strongly influenced by recurrent volcanic ash fal\. A model of paleoenvironmental development and changing geographic sceneries is also discussed. On the basis of paleobotanical and palynological data, a Barremian to Aptian age was previously suggested for the Baqueró Group. Recent isotopic datings confirm an Aptian age.